2020
DOI: 10.3390/ijms21030774
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Reveals the Different Response to Toxic Stress in Rootstock Grafted and Non-Grafted Cucumber Seedlings

Abstract: Autotoxicity of root exudates is one of the main reasons for consecutive monoculture problem (CMP) in cucumber under greenhouse cultivation. Rootstock grafting may improve the tolerance of cucumber plants to autotoxic stress. To verify the enhanced tolerance to autotoxic stress and illuminate relevant molecular mechanism, a transcriptomic comparative analysis was performed between rootstock grafted (RG) and non-grafted (NG) cucumber plants by a simulation of exogenous cinnamic acid (CA). The present study conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Cinnamic acid, ferulic acid, p-hydroxybenzoic acid and p-coumaric acid were demonstrated as main autotoxic substances in cucumber, and they have an adverse effect on growth, physiology and soil microbial communities ( Ye et al, 2006 ; Zhou & Wu, 2012 ; Zhou, Yu & Wu, 2012 ; Zhou & Wu, 2018 ). Our previous study also proved the detrimental effect of cinnamic acid on cucumber ( Xiao et al, 2020 ). Biosynthesis of phenolic and other aromatic acids undergoes the general phenylpropanoid pathway (GPP) and subsequent specific branch pathways.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Cinnamic acid, ferulic acid, p-hydroxybenzoic acid and p-coumaric acid were demonstrated as main autotoxic substances in cucumber, and they have an adverse effect on growth, physiology and soil microbial communities ( Ye et al, 2006 ; Zhou & Wu, 2012 ; Zhou, Yu & Wu, 2012 ; Zhou & Wu, 2018 ). Our previous study also proved the detrimental effect of cinnamic acid on cucumber ( Xiao et al, 2020 ). Biosynthesis of phenolic and other aromatic acids undergoes the general phenylpropanoid pathway (GPP) and subsequent specific branch pathways.…”
Section: Discussionmentioning
confidence: 54%
“…Previous studies demonstrated that autotoxicity is the main causes of consecutive monoculture problem ( Yu & Matsui, 1994 ; Yu et al, 2003 ). Cinnamic acid, as the main autotoxin, was used to simulate autotoxic stress, and the inhibitory effect on growth was confirmed ( Ye et al, 2006 ; Yu et al, 2003 ; Xiao et al, 2020 ). Although similar result were obtained in the present study, plant biomass of root-grafted cucumber seedlings was barely inhibited; similar findings were reported in eggplant ( Chen et al, 2011 ) and watermelon ( Ling et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the highly conserved domains and their evolutionary relationships, this superfamily is mainly divided into 20-25 subfamilies in agronomically important plants. A wide range of extensive studies have been reported on the bHLH superfamily-related genes in plant species after genome sequences have been produced, including cucumber [5], Arabidopsis [7], apple [10], tomato [24] and Carthamus tinctorius [32]. Additionally, functional and structural characterizations of most plant bHLH proteins have been described in detail.…”
Section: Discussionmentioning
confidence: 99%
“…The bHLH TFs have various functions in plant growth and development. The bHLH genes SPATULA and ALCATRAZ impact the development of carpel and fruit [5,6], and MYC2, MYC3, while the MYC4 affects the owering of Arabidopsis thaliana [7]. The bHLH gene BIGPETALp in A. thaliana plays an important role in controlling petal size [8], and the bHLH gene BIM1 is associated with embryonic patterning [9].…”
Section: Introductionmentioning
confidence: 99%